Three decades of Chondrichthyan research in Brazil assessed from conferences’ abstracts: patterns, gaps, and expectations - Soares, Karla D. A. (2023)
Of the almost 1,300 currently known Chondrichthyan species, 13.4% occur in Brazilian marine and freshwater environments and more than a half are under extinction threat. There are three main scientific events in Brazil committed to present and discuss research on fishes (including Chondrichthyes): EBI, SBEEL, and ISPCNF. We analyzed 1,584 submitted abstracts to these events over the last 30 years and noticed that, within Chondrichthyes, studies regarding Systematics were less representative (17%). However, the most shocking result concerned the proportion of women in authorship: almost 30% of abstracts were co-authored only by men, and only 25% of those in Chondrichthyan Evolution had women as last authors, demonstrating that a few women are acting as principal investigators in this area of research in Brazil since they might be leaving academia due to lack of support. Besides, the orders Carcharhiniformes and Myliobatiformes represented 66.9% of all studied taxa throughout the years, revealing a research bias on studied taxa which in turn has impacted directly on our knowledge of Chondrichthyan biodiversity and conservation planning. Most importantly, the neglected area of taxonomy needs to be enhanced to allow for appropriate species identification and threatening status evaluation.